2011
DOI: 10.1063/1.3650238
|View full text |Cite
|
Sign up to set email alerts
|

Potential candidates for hyperhalogens: A comparative study of BO2, AlO2, and VO3 species

Abstract: Recent work has shown that BO(2) which is a superhalogen with an electron affinity of 4.46 eV, can be used as building block of a new class of molecules/clusters whose electron affinities can exceed that of BO(2). This class of molecules was named hyperhalogens and the concept was illustrated by focusing on Au(BO(2))(2). Here we explore other superhalogens besides BO(2) to see if they too can be used to form hyperhalogens. We have chosen to focus on AlO(2) which is valence isoelectronic with BO(2) as well as V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 33 publications
6
41
0
Order By: Relevance
“…18 Therefore, the electron affinities (EAs) of hyperhalogens are much higher than those of their superhalogen building blocks. Further theoretical calculations on high EA species suggested that Na(BO 2 ) 2 , 19 and Mn 4 Cl 9 24 can also be considered as hyperhalogens. 25 In a recent theoretical study, Anusiewicz 26 predicted that various acidic functional groups (ClO 4 , ClO 3 , NO 3 , HSO 4 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…18 Therefore, the electron affinities (EAs) of hyperhalogens are much higher than those of their superhalogen building blocks. Further theoretical calculations on high EA species suggested that Na(BO 2 ) 2 , 19 and Mn 4 Cl 9 24 can also be considered as hyperhalogens. 25 In a recent theoretical study, Anusiewicz 26 predicted that various acidic functional groups (ClO 4 , ClO 3 , NO 3 , HSO 4 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Large deviation of OVGF results has been reported for binuclear superhalogen anions [Mg 2 (CN) 5 ] −1 when compared with high-level CCSD(T) calculations. 33,44 Therefore, besides the direct OVGF calculations, the indirect approach consisted of subtracting the anion energies from those of the neutral at the same level 15,20,22,33,40,52,61 has been performed with HF, MP2, CCSD and CCSD(T) 27 methods.…”
Section: Introductionmentioning
confidence: 99%
“…More recently,J ena and co-workers [40] proposed the concept of hyperhalogens as an ew class of highly electronegative species, in which the peripheral halogen atoms in at ypical superhalogen are replaced with the superhalogen moiety BO 2 .T he electron affinities of hyperhalogens can even surpass those of their superhalogen ligands. Am ultitude of hyperhalogens have been reported since 2010, such as Au(BO 2 ) 2 , [40] Cu(BO 2 ) 2 , [41] Na(BO 2 ) 2 , [42] Al(BO 2 ) 4 , [43] Ag(BO 2 ) 2 , [44,45] and Al(BF 4 ) 4 , [46] as well as the "magnetic hyperhalogens" Mn(BO 2 ) n and Fe(BO 2 ) n (n = 3, 4), [47] and "aromatich yperhalo-Based on the density functional theory for exchange-correlation potential, fluorocarbon molecular cages are investigated as buildingb locks of hyperhalogens. By utilizing C 8 F 7 as al igand,aseries of hyperhalogen anions, that is, M(C 8 F 7 ) 2 À (M = Li, Na, and K) and M(C 8 F 7 ) 3 À (M = Be, Mg, and Ca), are modeled.…”
Section: Introductionmentioning
confidence: 99%